RELATIONSHIP BETWEEN LEXICAL AND SEMANTICAL FEATURES OF ENGLISH AND UZBEK SPORT TERMS (American Journal of Interdisciplinary Research and Development, 2024)
This article deals with analyzing relationship between lexical and semantic features of sport terms. As well as synonyms and antonyms are considered as universal linguistic phenomena in sport terminological system. Numerous new sport terms and neologisms are penetrating into Uzbek languages from other foreign languages. Their translation problems and lexicographical unification issues also should be taken into account in the process of globalization and integration period.